Alcohol and Illicit Drug Use Are Important Factors for School-Related Problems among Adolescents - Heradstveit, Ove; Skogen, Jens C.; Hetland, Jørn; Hysing, Mari (Frontiers in Psychology, 2017)
The aim of this study was to investigate the association between alcohol and drug use, and school-related problems measured by low grade point average (GPA) and high school attendance. We also examined potential confounding effects from mental health problems. Although the issue is not new within current literature, the present study has its strengths in a large number of participants and the utilization of registry-based data on school-related functioning. A cross-sectional design is employed in this study using data from a large population-based sample of adolescents, youth@hordaland, in a linkage to official school registry data, and the current study presents data from N=7,874. The main independent variables were alcohol use and drug use, as well as potential alcohol- and drug-related problems. The dependent variables were registry-based school attendance and grades. All the alcohol- and drug measures included were consistently associated with low GPA (Odds ratios (OR) ranging 1.82 to 2.21, all p<0.001) and high levels of missed days from school (ORs ranging 1.79 to 3.04, all p<0.001) and high levels of hours missed from school (ORs ranging 2.17 to 3.44, all p<0.001). Even after adjusting for gender, age, socioeconomic status and mental health problems all the associations between alcohol and illicit drug use and the school-related outcomes remained statistically significant. Increasing number of indications on alcohol/drug-related problems and increasing levels of alcohol consumption were associated with more negative school-related outcomes. The results suggest that alcohol- and drug use, and particularly alcohol/drug-related problems, are important factors for school-related problems independently of mental health problems.